Mediaculture in historical changes (Herald of Journalism, 2019)
The main purpose of the article is to analyze the compatibility of the media and culture, the role and aspects of culture in the media. The object of the study is to identify the disadvantages and advantages of culture with the help of media technologies and to demonstrate the relationship of media culture with the media. The role of media culture in society, its social and moral, psychological and intellec-tual aspects is growing at an unprecedented pace, being a necessary means of developing the society surrounding its social, moral, psychological, moral, intellectual aspects. The article discusses various approaches to creating a unique information space using media media technology, as well as a feature of media cultural activities is considered as a factor contributing to the active formation of the media. Media culture – analyzing and evaluating texts covered on the topic of media in the media, can work as a multi-level system of personal development, capable of mastering new media knowledge through the media. We rely on the understanding of modern scholars who describe the culture as promoted by media technologies. And also in the information space it is considered that the mass media analyzes the culture of society and its implementation of functions.
Keywords: information, media, mediatization, mediaculture, mass media, mass communications.